Analysis of the Soil Erosion Hazard Level on the East Coast of Minahasa (Case Study of Kombi District) - Sandra E. Pakasi; Wiske C. Rotinsulu; Juliet M. Eva Mamahit; Melisa P. Todingan (Jurnal Agroekoteknologi Terapan, 2022)
The development of the Minahasa East Coast area into a tourism area has caused a tendency to change land use. Kombi Subdistrict is one of the areas on the East Coast of Minahasa that has experienced changes in land use with many investors building tourism areas there. The rate of land clearing in the area can accelerate the process of erosion. This research was carried out with the aim of knowing the level of soil erosion hazard on the East Coast of Minahasa, especially in Kombi District, in order to prevent soil damage so that environmental sustainability can be maintained and the development of tourism areas in the area can continue. The method used in this research is the overlay method for making digital maps and calculating erosion using the USLE method. The results of the analysis show that the Minahasa East Coast area, especially in Kombi District, has a light erosion hazard level of 1492.10 Ha, a moderate erosion hazard level of 5036.35 Ha, and a severe erosion hazard level of 6970.94 Ha. Keywords: erosion hazard level, soil Abstrak Pengembangan kawasan Pantai Timur Minahasa menjadi kawasan pariwisata, menyebabkan kecenderungan terjadi perubahan pemanfaatan lahan. Kecamatan Kombi adalah salah satu wilayah di Pantai Timur Minahasa yang mengalami perubahan penggunaan lahan dengan banyaknya investor yang membangun kawasan pariwisata di sana. Lajunya pembukaan-pembukaan lahan di daerah tersebut, dapat mempercepat proses terjadinya erosi. Penelitian ini dilaksanakan dengan tujuan mengetahui tingkat bahaya erosi tanah di Pantai Timur Minahasa khususnya di Kecamatan Kombi agar dapat mencegah kerusakan tanah sehingga kelestarian lingkungan dapat terjaga dan pengembangan kawasan pariwisata di daerah tersebut dapat berlanjut. Metode yang digunakan dalam penelitian ini adalah metode overlay untuk pembuatan peta digital dan perhitungan erosi menggunakan metode USLE. Hasil analisis menunjukkan kawasan Pantai Timur Minahasa khususnya di Kecamatan Kombi memiliki tingkat bahaya erosi ringan seluas 1492.10 Ha, tingkat bahaya erosi sedang seluas 5036.35 Ha, dan tingkat bahaya erosi berat seluas 6970.94 Ha. Kata Kunci : tingkat bahaya erosi, tanah